The Effect of Goat Milk Substitution with Sunflower Seed Extract (Helianthus annuus L.) on the Production of Optima Kefir on pH, Total LAB, and Total Yeast - Azhari, Dinda Tri; Wulandari, Eka; Pratama, Andry (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Goat milk has a distinctive “goaty”, making it a limitation for fresh consumption. Processing the goat milk into kefir can extend the shelf life and minimize the smell of goat milk. Kefir is a fermented milk product after pasteurization then added kefir grain starter. This study aims to determine the effect of goat milk substitution with sunflower seed extract (Helianthus annuus. L) in the production of optima kefir on pH, total LAB, and total yeast. Conducted in November 2024 at the Livestock Product Processing Technology Laboratory and Biotechnology Research and Testing Laboratory, Faculty of Animal Husbandry, Padjadjaran University, Sumedang. The research method was conducted experimentally using a completely randomized design (CRD) with 5 treatments and 4 replicates. The treatments consisted of the ratio of goat milk and sunflower seed extract P1 (80:20), P2 (60:40), P3 (50:50), P4 (40:60), and P5 (20:80). Data processing of research results using Analysis of Variance and Duncan's Multiple Range Test. The results showed that the treatment consisted of goat milk and sunflower seed extract had a significant effect (P<0.05) on total LAB and total yeast, and was able to produce the best kefir in the P2 (60:40) treatment with a pH value of 3.99, total LAB 16.32  108 CFU/mL and total yeast 17.35  109 CFU/mL.